Capitalisation of accessibility to dockless bike sharing in housing rentals: Evidence from Beijing. (January 2021) - Qiao, Si; Gar-On Yeh, Anthony; Zhang, Mengzhu
Highlights: Docklessness has successfully reworked shared bikes into desired and valuable amenity. There is unequal accessibility to dockless bike sharing in Beijing. Every one-point increase in the accessibility to dockless bike sharing generates a premium worth 28.02 CNY in housing rental, The benefits of dockless bike sharing are gradually eroded and transferred to landlords through rental premiums. Abstract: Chinese cities have seen a rapid development of dockless bike sharing (DBS) in recent years. Numerous studies have examined the positive social effects of DBS, but a crucial question remains: if docklessness has successfully reworked shared bikes into a desired and valuable amenity, will unequal access to DBS affect housing rentals? The present study examines this question by considering the case of Beijing. A big data approach is employed to analyse the listed rents of 75, 197 houses in Beijing and their attributes that affect housing rentals. Measurement of accessibility to DBS at the housing level is constructed from 3.2 million DBS trips generated over two weeks. Results of the hedonic model show that every one-point increase in the accessibility to DBS generates a premium worth 28.02 CNY in housing rental, thereby supporting the hypothesis that docklessness has turned DBS into a valuable amenity for renters. These findings suggest that although low- and middle-income workers benefit from the convenience of DBS in the short term, the benefits are gradually eroded and transferred to landlords through rental premiums. Unequal accessibility to DBS may induce gentrification that displaces or excludes low-income renters in certain neighbourhoods.